EFEKTIVITAS LAYANAN BIMBINGAN KARIER DALAM MENINGKATKAN KEMAMPUAN PERENCANAAN KARIER SISWA - Wirastania, Aniek; Lianawati, Ayong; Hartanti, Jahju; Jannah, Aiza Uslifatul; Arista, Bella (Kanigara, 2022)
Students who have good career planning are usually characterized by characteristics such as having (1) understanding of the world of work, (2) special interests and talents in a particular world of work, (3) personality and values ​​related to careers. Career guidance services are guidance given to students and focused on providing assistance, especially in planning, developing, solving various career-related problems, and providing an understanding of the work in a position. Based on the implementation of community service activities, a result is obtained that this career guidance and counseling service activity can improve the ability to carry out career planning properly according to the talents and interests of students.